Purifikasi L-Asparaginase Dari Bawang Bombay (Allium cepa L.) Menggunakan Kromatografi Filtrasi Gel Sephadex G-100 - Setiawan, Ayu Sri Rahayu (Chem Info Journal, 2013)
L-asparaginase from onion (Allium cepa L.) was purified. Some stage of the work including isolation of L-asparaginase obtain of crude extract was further fractionated with ammonium sulphate, dialysis, and gel filtration chromatography Sephadex G-100 to produce L-asparaginase with a higher purity. Analysis of L-asparaginase in the crude extract, the ammonium sulphate fractionation, and results of gel filtration chromatography Sephadex G-100 is done by determining the activity of the enzyme with Nessler method and determination of protein content by Lowry method so it can be determined the specific activity. The analysis obtained are a crude extract of L-asparaginase from onion (Allium cepa L.) with a specific activity of 30.502 units/mg protein. The highest specific activity of the fraction of ammonium sulphate is at F5 (80-100%) of 30.831 units/mg protein. F5 was further purified by gel filtration chromatography sephadex G-100, obtained the highest specific activity was in fraction 10 by 6508.250 units/mg protein with a purity level more than 200 times compared to the crude extract.